Evaluation of Distinct Freezing Methods and Cryoprotectants for Human Amniotic Fluid Stem Cells Cryopreservation. (14th May 2012) - Janz, Felipe de Lara; Debes, Adriana de Aguiar; Cavaglieri, Rita de Cássia; Duarte, Sérgio Aloísio; Romão, Carolina Martinez; Morón, Antonio Fernandes; Zugaib, Marcelo; Bydlowski, Sérgio Paulo
Abstract : Amniotic fluid (AF) was described as a potential source of mesenchymal stem cells (MSCs) for biomedicine purposes. Therefore, evaluation of alternative cryoprotectants and freezing protocols capable to maintain the viability and stemness of these cells after cooling is still needed. AF stem cells (AFSCs) were tested for different freezing methods and cryoprotectants. Cell viability, gene expression, surface markers, and plasticity were evaluated after thawing. AFSCs expressed undifferentiated genes Oct4 and Nanog; presented typical markers (CD29, CD44, CD90, and CD105) and were able to differentiate into mesenchymal lineages. All tested cryoprotectants preserved the features of AFSCs however, variations in cell viability were observed. In this concern, dimethyl sulfoxide (Me2 SO) showed the best results. The freezing protocols tested did not promote significant changes in the AFSCs viability. Time programmed and nonprogrammed freezing methods could be used for successful AFSCs cryopreservation for 6 months. Although tested cryoprotectants maintained undifferentiated gene expression, typical markers, and plasticity of AFSCs, only Me2 SO and glycerol presented workable viability ratios.